Psychometric evaluation of the Chinese version of alcohol relapse risk scale (C-ARRS) in patients with alcohol use disorder - Lee, I-Ting; Liao, Po-Chiao; Liu, Tung-Hsia; Ogai, Yasukazu; Chang, Hu-Ming; Liu, Yu-Li; Huang, Ming-Chyi (Alcohol (Fayetteville, N.Y.), 2024)
Alcohol use disorder (AUD) is recognized as a chronic relapsing disorder. Alcohol Relapse Risk Scale (ARRS), a multidimensionally self-rating scale, was developed initially by the Japanese to assess the risk of alcohol reuse. The study aimed to validate the reliability and factor structure of the Chinese version of the ARRS (C-ARRS) for patients with AUD. A total of 218 patients diagnosed with AUD according to DSM-5 were recruited for self-administering C-ARRS. We assessed the internal consistency of C-ARRS using Cronbach's α coefficients and examined the factor structure through confirmatory factor analysis (CFA). Additionally, we investigated the concurrent validity by correlating C-ARRS with the Visual Analog Scale of Alcohol Craving (VAS), Penn Alcohol Craving Score (PACS), Beck Depression Inventory (BDI), and Beck Anxiety Inventory (BAI) scores. CFA demonstrated inadequate data fit for the original 32-item C-ARRS, prompting the development of a revised 27-item version consisting of 6 subscales with satisfactory model fit estimates. The 27-item C-ARRS exhibited favorable internal consistency, with Cronbach's α ranging from 0.611 to 0.798, along with adequate factor loadings. The 27-item C-ARRS scores displayed significant correlations with the scores of VAS, PACS, BDI and BAI (p < .001). Our results indicated favorable reliability and factor structure of the 27-item C-ARRS. The significant correlation between the 27-item C-ARRS and clinical measures (such as depression, anxiety, and craving) demonstrates satisfactory concurrent validity. These observations collectively support the feasibility of using 27-item C-ARRS to assess the risk of alcohol relapse in patients with AUD. •AUD is a prevalent psychiatric disorder characterized by a high rate of relapse.•No tools are available in Chinese to assess the relapse risk in patients with AUD.•We validated the 32-item Chinese version of Alcohol Relapse Risk Scale (CARRS).•The modified 27-item C-ARRS version exhibits satisfactory reliability and validity.•C-ARRS could provide information on relapse risk and facilitate early treatment.